Interest Rate Policies in Developing Countries. (Occasional Papers; Occasional Paper ;, 1983)
In recent years, the appropriate level and structure of interest tates have come to be seen as major issues in connection with stabilization programs undertaken by members. These issues arise from consideration both on the demand side, as interest rates affect the magnitude of aggregate demand, and on the supply side, as they influence the volume and quality of investment and, thus, the growth of output.